(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Secoisolariciresinol diglucoside (SDG) is a plant lignan mainly found in dietary food and various plants. It belongs to a bioactive polyphenolic chemical class. SDG and its metabolites (mammalian enterolignan) are having various pharmacological activities, viz., antioxidant, partial agonist to estrogen receptor and inhibitor of tyrosine kinase and topoisomerase. Although, human studies are limited, its pharmacological actions explain its use in diabetes, atherosclerosis, breast cancer, colon cancer, prostate cancer and in cardiovascular disease.